Policy augmented scaling model for a fully validated CSAP-the happy seeder technology to curb air pollution and build resilience. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Innovation made in interest of sustainable development is transformed as scalable practice through business model underpinned by national policy. It has led to continuously improved value to services and product adapted to dynamic climate challenges. Residue burning has sensitized the public-private institutes to collaborate and pool national resources for scaling